MENINGKATKAN KEMAMPUAN BELAJAR MATEMATIKA PADA MATERI PENGUKURAN SISWA KELAS V SDN 01 NEGERI MULYO MELALUI NUMBERED HEAD TOGETHER (NHT) TAHUN 2017 - Sri Ariyani (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
Classroom Action Research was carried out starting from problem which writer face in the process of learning mathematics that is lack of ability of student in learning of measurement, so student interest in learning less and only part of student who able to reach KKM. The KKM of Mathematics subjects is 65. The purpose is to carry out the PTK that the authors report is to improve students’ abilities in learning measurements on mathematics subjects. The ability of the students appears in the interest and learning activities and student learning outcomes. The author tries to solve the problems encountered by applying the model of learning Numbered Heads Together (NHT) in implementing the learning process, arguing that NHT or shared thinking numbers apply cooperative learning types designed to influence student interaction patterns and as an alternative to traditional classroom structures. Each round consists of four stages: design, activity and observation, reflection and revision. The research target is the students of grade V SDN 01 Mulyo in the academic year 2017 / 2018. From the analysis result got that the student’s learning achievement has increased from start of pre cycle, cycle 1, cycle 2 until cycle 3, following percentage of mastery for six meeting of 26 students starting from pre cycle: 44, 36%; 53.85%; 57.69%; 69.23%; 76.92%; 88.46%; 92.31%. The conclusion of this research is that the application of Numbered Heads Together (NHT) model can increase learning activity of mathematics of grade V SDN 01Mulyo Gunung Labuhan Subdistrict of Way Kanan Regency.